Pengembangan Sistem Booking Web Real-Time dengan Kalender Monitoring dan Live Chat Tjahaja79 - ardiansyah, bangga aditya; Meimaharani, Rizkysari; Chamid, Ahmad Abdul (STMIK Banjarbaru, 2026)
The manual reservation process at Cafe Tjahaja79 often leads to operational inefficiency and a lack of transparency regarding table availability for customers. This study aims to develop a web-based booking system integrated with a real-time monitoring calendar and live chat to address these issues. The system development method employed is the Waterfall model, ranging from requirements analysis to implementation, while functionality testing was conducted using Black Box Testing. The system is designed to facilitate table reservations, digital payments via QRIS, and instant communication between customers and administrators. The test results indicate that all system features function validly and are free from functional errors. It is concluded that the implementation of this system effectively improves the efficiency of reservation management administration and provides service certainty for customers through accurate schedule visualization.Keywords: Online booking system; Table reservation; Live chat; Digital calendar; Waterfall. AbstrakProses reservasi manual di Cafe Tjahaja79 sering kali menyebabkan ketidakefisienan operasional dan minimnya transparansi informasi ketersediaan meja bagi pelanggan. Penelitian ini bertujuan mengembangkan sistem booking berbasis web yang terintegrasi dengan kalender monitoring real-time dan live chat untuk mengatasi permasalahan tersebut. Metode pengembangan sistem yang diterapkan adalah Waterfall, mulai dari analisis kebutuhan hingga implementasi, sedangkan pengujian fungsionalitas dilakukan menggunakan Black Box Testing. Sistem dirancang untuk memfasilitasi reservasi meja, pembayaran digital via QRIS, serta komunikasi instan antara pelanggan dan admin. Hasil pengujian menunjukkan bahwa seluruh fitur sistem berjalan valid dan bebas dari kesalahan fungsional. Disimpulkan bahwa implementasi sistem ini efektif meningkatkan efisiensi administrasi pengelolaan reservasi serta memberikan kepastian layanan bagi pelanggan melalui visualisasi jadwal yang akurat.